1999
DOI: 10.1152/ajpheart.1999.277.1.h107
|View full text |Cite
|
Sign up to set email alerts
|

Four different components contribute to outward current in rat ventricular myocytes

Abstract: In rat ventricle, two Ca2+-insensitive components of K+ current have been distinguished kinetically and pharmacologically, the transient, 4-aminopyridine (4-AP)-sensitive I to and the sustained, tetraethylammonium (TEA)-sensitive I K. However, a much greater diversity of depolarization-activated K+ channels has been reported on the level of mRNA and protein. In the search for electrophysiological evidence of further current components, the whole cell voltage-clamp technique was used to analyze steady-state ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
79
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 33 publications
18
79
0
Order By: Relevance
“…Therefore, acute inhibition of Kv2.1 would provide valuable new information. We have now extended our previous studies using a novel non-peptide compound (the bispidine derivative, C-1) related to class III antiarrhythmic agents such as tedisamil (35) that block delayed-rectifier K ϩ channels in the heart (36), of which Kv2.1 is a major component (37).…”
Section: Fig 3 C-1 Inhibits Kv21 Currents In Min6 Cellsmentioning
confidence: 91%
“…Therefore, acute inhibition of Kv2.1 would provide valuable new information. We have now extended our previous studies using a novel non-peptide compound (the bispidine derivative, C-1) related to class III antiarrhythmic agents such as tedisamil (35) that block delayed-rectifier K ϩ channels in the heart (36), of which Kv2.1 is a major component (37).…”
Section: Fig 3 C-1 Inhibits Kv21 Currents In Min6 Cellsmentioning
confidence: 91%
“…Earlier work by Himmel et al (21) provided a comprehensive analysis of the different current components by analyzing the inactivation characteristics of total outward currents in rat ventricular cells. They showed that a protocol consisting of 2,000-ms prepulses to potentials ranging from Ϫ140 to ϩ20 mV (in 10-mV steps except for the range of Ϫ60 and Ϫ20 mV, in which 5-mV steps were used), followed by test pulses to ϩ60 mV, allowed the measurement of steady-state inactivation of currents that could best be fit by two Boltzmann functions.…”
Section: Methodsmentioning
confidence: 99%
“…The channel proteins encoded by Kv4.2 and Kv4.3 underlie the transient outward current in rat ventricular cells (14,34). The sustained current has several components (21) and is the complex expression of several channel proteins (34). In our experiments, antibodies directed against Kv4.2, Kv1.2 (Alomone), and Kv4.3 (Alomone and an antibody kindly provided by Dr. J. Nerbonne) were used.…”
Section: Methodsmentioning
confidence: 99%
“…To make the model rat specific, the voltage-activated K ϩ channel representation of Winslow et al was replaced by a formulation representative of rat cardiac myocytes (16). This novel representation, as well as other minor changes on other currents, is discussed in detail in Tables 1-6.…”
Section: Ionic Channel Formulationmentioning
confidence: 99%